How the rural infrastructure construction drives rural economic development through rural living environment governance—case study of 285 cities in China - Du, Xuan; Jiao, Fangyi (Frontiers in Environmental Science, 2023)
With deepening of rural revitalization strategy, rural infrastructure construction plays an important role in living environment management and economic development. Based on the mediation model, this paper takes case study of 285 cities in China from 2017 to 2022 as samples, constructs the explanatory variable, the explained variables and the mediator variable by entropy method, empirically analyzes the impact of rural infrastructure construction on rural living environment governance and economic development, as well as the mediation role played by rural living environment governance. It is found that there is a significant positive impact between rural infrastructure construction and rural economic development, and rural infrastructure construction can promote economic development through rural living environment governance. Further analysis show that the impact of infrastructure on economic development presents heterogeneity, and the impacts of rural infrastructure construction on local economic development and on local economic development through living environment governance in the eastern and central China is stronger than that in the western China. After controlling a series of variables related to rural infrastructure, and performing endogeneity tests and robustness tests such as tail-shrinking regression and principal component analysis, the regression results are still robust. This paper firstly provides scientific empirical evidence for the hypothesis that rural infrastructure construction promotes economic development through living environment governance, and secondly confirms the necessity of strengthening infrastructure construction in China to promote rural revitalization, providing a policy basis for scientific decision-making, and finally finds an important way out to solve the problem of unbalanced economic development in rural areas to some extent.